Digital Payments as a Driver of Sustainable Consumption: A Consumer-Based Study of Perceived Challenges and Opportunities in FinTech Ecosystems - Surbhi Chugh; Rituraj Pant; Aayushi Upadhyay Pandey (International Journal of Optical Innovations & Research, 2026)
The Digital Payment Systems evolved remarkably fast, and so, have transformed the way in which the consumer makes purchases for products and services as well as the way in which they function economically, i.e., how they consume things. Beyond convenience and efficiency, digital payments are increasingly viewed as a potential driver of sustainable consumption by reducing cash dependency, improving transaction transparency, and supporting responsible spending practices. This study examines digital payments as a driver of sustainable consumption through a consumer-based analysis of perceived challenges and opportunities within fintech ecosystems. Using primary data collected from consumers, the research analyses usage patterns of digital payment systems, evaluates their influence on sustainable consumption behaviour, and identifies key challenges and opportunities affecting consumer trust and adoption. The findings highlight that while digital payments offer substantial opportunities in terms of convenience, financial inclusion, and environmental sustainability, concerns related to security, privacy, and trust continue to influence consumer perceptions. According to the report, the acceptance and efficient usage of digital payment systems are greatly impacted by demographic parameters including age, education, and digital literacy. It also emphasises how government programmes and legal frameworks may boost consumer trust and encourage broader use of digital transactions. The study contributes to the growing literature on sustainable fintech by providing insights for policymakers, fintech firms, and financial institutions to strengthen digital payment ecosystems and promote sustainable consumption.
Keywords: Eco-innovation; Regulations; Sustainable Consumption; consumer perceptions; digital payments; fintech